Retracted: Biochemical Evaluation of Adansonia Digitata Methanolic Leaf and Stem Bark Extract on Streptozotocin Induced Diabetic Rats - Ejeh, Yakubu Ojochenemi; Stephe, Ezeonu Chukwuma; Tsuvini, Jonah; Atah, David; Sunday, Gabriel; Samuel, Ishaya; David, Gideon (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Several herbal preparations are used to treat diabetes; however, their overall biochemical effects other than hypoglycemic effects are scanty. This study therefore was designed to evaluate the effect of methanolic extract of leaves and stem-bark of Adansonia digitata on biochemical indices of streptozotocin-induced diabetic rats. Sixty-three wistar rats were distributed into 9 groups of 7 each. The test animals were intraperitoneally administered with single dose of 50 mg/kg streptozotocin and monitored for 72 hours for development of hyperglycemia. Diabetic rats were treated in 12 h cycles for three weeks with 100 mg/kg, 200 mg/kg and 300 mg/kg of both leaves and stem-bark of Adansonia digitata methanolic extract and metformin (50 mg/kg). Non-diabetic control rats received a lacebo of distilled water. Group 1 served as normal control, group 2 served as diabetic control, while groups 4-9 were diabetic rats treated orally with methanolic leave and stem-bark extracts of Adansonia digitata (100 mg/kg, 200 mg/kg and 300 mg/kg) for 21days. Group 3 animals were diabetic rats treated with anti-diabetic drug (metformin 50 mg/kg). The levels of fasting blood sugar (FBS), electrolytes (Na+, K+, Cl-), Urea and creatinine Triglyceride (TG), Cholesterol (CHOL), thiobarbituric acid reactive substance (TBARS), White Blood Cell (WBC) count, Red Blood Cell (RBC) count, Haemoglobin (HGB), Hematocrit (HCT), Platelet (PLT), Mean Cell Volume (MCV), Mean Cell Haemoglobin (MCH), Mean Cell Haemoglobin Concentration (MCHC), Lymphocyte (LYM), aspartatate aminotransfrease (AST), alanine aminotransferase (ALT), total protein (TP), albumin (ALB), catalase (CAT) and superoxide dismutase (SOD) activities total, total bilirubin (TB), direct bilirubin(DB) and indirect bilirubin (IB) concentrations were assayed. The results indicated that the concentrations of Na+, K+, Cl-, creatinine, urea TBARS, ALT, AST, ALB, CHOL and IB bilirubin were significantly (p<0.05) increased, while the levels of WBC, RBC, HGB, HCT, PLT, LYM, MCV SOD and CAT were reduced in the diabetic control (p<0.05). The Adansonia digitata methanolic leaves and stem-bark extract significantly increased WBC, RBC, HGB, HCT, PLT, MCV, LYM, TP, CAT and SOD activity and reduced the FBS, Na+, K+, Cl-, TBARS, ALT, AST, creatinine, urea and bilirubin concentrations significantly (p<0.05) compared to normal control. However, treatment with metformin showed slight modification in the changes observed compared to Adansonia digitata methanolic leaves and stem-bark extract. MCV and MCHC reduced non-significantly (p>0.05) in the diabetic animals as compared to the normal control and the extract-treated rats, while they increased non- significantly (p>0.05) in the test groups when compared to the diabetic control. Levels of TB, DB, and TG showed non-significant (p<0.05) increase in diabetic control, but treatment with extracts and metformin caused non-significant decrease (p<0.05). Diabetic control exhibited significantly (p<0.05) decreased ALB levels and non-significant TP decrease compared to normal control, while Adansonia digitata extracts and metformin significantly increased ALB and non-significantly increased TP levels compared to diabetic control. The study concluded that Adansonia digitata extracts reversed diabetes-induced oxidative stress in rat hepatocytes, potentially through beta cell regeneration or insulin release stimulation, suggesting their potential for managing diabetic complications.